Coronary atherosclerosis and chemotherapy: From bench to bedside - Fanghui Zhou; Xinxin Zhu; Yao Liu; Yue Sun; Ying Zhang; Dechun Cheng; Wei Wang (Frontiers in Cardiovascular Medicine, 2023)
Cardiovascular disease, particularly coronary artery disease, is the leading cause of death in humans worldwide. Coronary heart disease caused by chemotherapy affects the prognosis and survival of patients with tumors. The most effective chemotherapeutic drugs for cancer include proteasome inhibitors, tyrosine kinase inhibitors, immune checkpoint inhibitors, 5-fluorouracil, and anthracyclines. Animal models and clinical trials have consistently shown that chemotherapy is closely associated with coronary events and can cause serious adverse cardiovascular events. Adverse cardiovascular events after chemotherapy can affect the clinical outcome, treatment, and prognosis of patients with tumors. In recent years, with the development of new chemotherapeutic drugs, new discoveries have been made about the effects of drugs used for chemotherapy on cardiovascular disease and its related mechanisms, such as inflammation. This review article summarizes the effects of chemotherapeutic drugs on coronary artery disease and its related mechanisms to guide efforts in reducing cardiovascular adverse events during tumor chemotherapy, preventing the development of coronary heart disease, and designing new prevention and treatment strategies for cardiotoxicity caused by clinical tumor chemotherapy.